Point-of-Care Based Electrochemical Immunoassay for Epstein-Barr Virus Detection - Miao Yu; Ming Liu; Yuan Li (Journal of Analytical Methods in Chemistry)
This work describes a label-free electrochemical immunosensor for the sensing of Epstein-Barr virus (EBV) with high sensitivity. First, a monolayer of 1,6-hexanedithiol (HDT) was fabricated on the screen-printed electrode surface by the interaction between sulfur atoms and SPE. AuNPs can be modified on the electrode by the Au-S bond formed between the HDT-free group and Au atom in AuNPs. Protein A is then adsorbed onto AuNPs. Several parameters were optimized. The optimum concentration of protein A is 0.6 mg/mL. The optimum immobilization time for protein A is 90 min. The optimum concentration of antibody is 80 μg/mL. The optimum immobilization time for antibody is 90 min. Directional immobilization of EBV antibody is achieved by high affinity binding of protein A to the Fc segment of antibody. When antigen specifically binds to antibody, the formation of immune complexes blocks electron transfer of [Fe(CN)6]4-/3- and is reflected in the detection of cyclic voltammetry/electrochemical impedance spectroscopy. The detection range is 1 pg/mL–l00 ng/mL with a LOD of 0.1 pg/mL. In addition, the proposed sensor exhibited an excellent antiinterference property.